Intracardiac migration of ureteral double-J stent: A case report and review - Farshi, Ali Reza; Roshandel, M. Reza (Canadian Urological Association Journal, 2015)
Ureteral double-J (DJ) stenting is a common urologic procedure in several ureteral surgeries and has been used to manage ureteral obstructions during pregnancy. It may result in early and late complications. We review a rare case of migration of the DJ stent into the cardiovascular system in a pregnant female. We also review the literature. The endoscopic procedure to remove this displacement has been done postnatally with no adverse effects.